The Effects of Vermicompost Dosage Applied at Different Times on the Growth and Yield of Sweet Corn - Mayasari, Mutia; Sudjatmiko, Sigit; Pujiwati, Hesti (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2024)
The cultivation of sweet corn currently relies on inorganic nutrient inputs, which often lead to excessive use of fertilizers and subsequent land degradation. To address this issue while maintaining land productivity, researchers have explored the application of vermicompost fertilizer, known for its positive impact on soil physical, chemical, and biological properties. The aims of study were to determine the vermicompost fertilizer doses applied at different times to enhance sweet corn growth and yield. The research was arranged in a completely randomized block design with a single factor by combining the doses of vermicompost (50% to 100%) and variations of application times (one to two weeks before planting). Each treatment was replicated three times. The results revealed that the 100% vermicompost applied two weeks before planting showed the highest increased on the plant height, leaf numbers, and the husk cob weight. The application of vermicompost as organic fertilizer on sweet corn cultivation enhanced the productivity of sweet corn. Keywords: application times, environmental safety, organic farming, sweet corn, vermicompost